Pengaruh Penerapan Sistem Penjaminan Mutu Internal dan Kepemimpinan Kepala Sekolah Terhadap Peningkatan Mutu Layanan Pendidikan - Lynda Takamsi; Safari Safari; Eliyanti Agus Mokodompit (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of the implementation of the Internal Quality Assurance System (SPMI) and principal leadership on the quality of educational services in South Konawe Regency, Southeast Sulawesi. The research employed a quantitative descriptive approach with a survey design to obtain an empirical overview of the relationships among the variables examined. The population consisted of all principals at the elementary, junior high, senior high, and vocational high school levels, totaling 70 respondents. The sampling technique used purposive sampling based on specific criteria relevant to the research objectives. Data were collected through questionnaires that had been tested for validity and reliability to ensure the accuracy and consistency of the research instrument. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25.0. Prior to hypothesis testing, classical assumption tests were performed, including normality, multicollinearity, and heteroscedasticity tests, to ensure the feasibility of the regression model. Furthermore, the F-test was conducted to examine the model’s overall significance, while the t-test was used to determine the partial effect of each independent variable on the dependent variable. The results indicate that the implementation of SPMI and principal leadership have a positive and significant effect on the quality of educational services. These findings highlight the importance of strengthening managerial capacity and internal commitment in implementing SPMI, as well as enhancing principal leadership quality to continuously improve educational service standards and overall education quality.